Nauczanie i wychowanie w pracy z pacjentami chorymi na schizofrenię - Witusik, Andrzej; Pietras, Tadeusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The purpose of this paper is to discuss the role of pedagogical work in the rehabilitation of patients with schizophrenia. The article discusses ways of rehabilitation of patients with schizophrenia taking into account the importance of teachers work. This model developed G. Thornicroft and coworkers and it is called the matrix model.